Caveolin 1 in bovine liver is associated with fatty acid–induced lipid accumulation and the endoplasmic reticulum unfolded protein response: Role in fatty liver development - Ming Li; Bichen Zhao; Jingyi Wang; Huijing Zhang; Yue Yang; Shihao Song; Androniki Psifidi; Wenda Wu; Juan J. Loor; Chuang Xu (Journal of Dairy Science)
ABSTRACT: Disruption of endoplasmic reticulum (ER) homeostasis (i.e., ER stress) is intrinsically linked with lipid metabolism disorders in dairy cows. Caveolin 1 (CAV1) is a ubiquitously expressed membrane-associated scaffolding protein involved in regulating the secretory pathway within the ER. Whether inhibiting the activity of CAV1 affects the ER and its potential role in hepatic lipid deposition in dairy cows is unknown. Biopsies of liver tissue from Holstein cows (median DIM = 13 d, range = 5–21 d) diagnosed as healthy (n = 6; hepatic triacylglycerol (TAG) levels <1%; median milk production = 38.9 kg/d, interquartile range = 38.0–40.8 kg/d) or suffering from fatty liver (n = 6; hepatic TAG levels >5%; median milk production = 36.6 kg/d, interquartile range = 35.7–38.1 kg/d) revealed that fatty liver was associated with lower abundance of the CAV1 gene and protein, higher phosphorylation (p) levels of PERK and IRE1α, and increased abundance of the ATF6, GRP78, and CHOP proteins, and several unfolded protein response (UPR) genes (ATF4, sXBP1, and GRP78). Proteins related to de novo fatty acid synthesis, including ACC1, SREBP-1c, PPARγ, and downstream targets genes of SREBP1 (ACACA and FASN) also had greater abundance. This in vivo analysis highlighted a mechanistic link between CAV1 protein abundance, ER stress, and lipid metabolism in fatty liver. A mechanistic study was then performed in vitro with primary hepatocytes isolated from 5 healthy calves (weight = 40–45 kg; 1 d old). Initially, hepatocytes were treated with free fatty acid (FFA; 1.2 mM) for 1, 3, 6, or 12 h. Treatment with FFA reduced CAV1 protein abundance linearly while reducing abundance of ER stress-related proteins, phosphorylated [p-] IRE1α, p-PERK, GRP78, ATF6, and CHOP. Proteins related to de novo fatty acid synthesis (ACC1, SREBP-1c, PPARγ) also increased linearly, and lipid droplets accumulated progressively over time following FFA treatment. Subsequently, to assess the role of CAV1 in FFA-induced ER stress and de novo fatty acid synthesis, hepatocytes were transfected with pCMV-CAV1 (cattle)-3 × FLAG-Neo (plasmid construct [pc-]CAV1) plasmid to overexpress CAV1 or with siRNA to silence CAV1 (siCAV1) transcription. Overexpression of CAV1 alleviated ER stress by reducing levels of p-PERK and p-IRE1α, as well as protein abundance of ATF6, GRP78, CHOP, and several UPR genes (GRP78, ATF4, and sXBP1). Similarly, CAV1 overexpression decreased protein abundance of ACC1, SREBP-1c, PPARγ, and downstream targets genes of SREBP1 (ACACA and FASN). Conversely, silencing CAV1 exacerbated FFA-induced ER stress and de novo fatty acid synthesis. Considering the negative role of FFA-induced ER stress on lipid accumulation in hepatocytes, a second in vitro experiment involved hepatocytes treated with 0.5 μg/mL tunicamycin (TM; a typical ER stress inducer) for 24 h with or without overexpressing CAV1 (pc-CAV1). Overexpressing CAV1 reversed TM-induced increases in mRNA and protein associated with ER stress and de novo fatty acid synthesis. Furthermore, use of hepatocytes transfected with pc-CAV1 for 48 h and subjected to co-immunoprecipitation revealed that CAV1 interacts with IRE1α and ATF6. Overall, the data suggest that CAV1 may help reduce hepatic ER stress and mitigate fatty acid synthesis by binding to and inhibiting IRE1α and ATF6 signaling.